2011
DOI: 10.11646/zootaxa.3025.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater prawns of the genus Macrobrachium Bate, 1868 (Crustacea, Decapoda, Palaemonidae) from Laos

Abstract: Caridean prawns of the genus Macrobrachium Bate, 1868 (Crustacea, Decapoda, Palaemonidae) collected from the Laotian river system were studied. Fourteen species are recognised in this study, including one unidentified species. Their taxonomy is discussed and illustrated, of which 11 species are new records to the Laotian fauna. The identity of species of the “M. dienbienphuense” group has been remained obscure, and this study, which incorporated the 16S rRNA mitochondrial gene analysis, demonstrated that M. am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 0 publications
4
45
0
1
Order By: Relevance
“…Twenty-eight described species of freshwater prawns of the genus Macrobrachium Spence Bate, 1868 have been reported in Thailand (Cai et al 2004;Naiyanetr 2001;Naiyanetr 2007;Saengphan et al 2018;Saengphan et al 2019). All Macrobrachium species in Thailand are found abundantly within two major riverine systems, namely the Chaophraya and Greater Mekong Basins, as reported by previous taxonomic studies (Cai & Ng 2002;Hanamura et al 2011). Cai et al (2004) reported that the M. pilimanus species group sensu Johnson (1960) consisted of 12 species: M. pilimanus (De Man, 1879), M. leptodactylus (De Man, 1892), M. hirsutimanus (Tiwari, 1952), M. dienbienphuense Dang and Nguyen, 1972, M. eriocheirum Dai, 1984 (currently treated as a synonym of M. dienbienphuense), M. ahkowi Chong and Khoo, 1987, M. gua Chong, 1989, M. forcipatum Ng, 1995 Ou and Yeo, 1995, M. pilosum Cai and Dai, 1999, M. amplimanus Dai, 1999, andM.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Twenty-eight described species of freshwater prawns of the genus Macrobrachium Spence Bate, 1868 have been reported in Thailand (Cai et al 2004;Naiyanetr 2001;Naiyanetr 2007;Saengphan et al 2018;Saengphan et al 2019). All Macrobrachium species in Thailand are found abundantly within two major riverine systems, namely the Chaophraya and Greater Mekong Basins, as reported by previous taxonomic studies (Cai & Ng 2002;Hanamura et al 2011). Cai et al (2004) reported that the M. pilimanus species group sensu Johnson (1960) consisted of 12 species: M. pilimanus (De Man, 1879), M. leptodactylus (De Man, 1892), M. hirsutimanus (Tiwari, 1952), M. dienbienphuense Dang and Nguyen, 1972, M. eriocheirum Dai, 1984 (currently treated as a synonym of M. dienbienphuense), M. ahkowi Chong and Khoo, 1987, M. gua Chong, 1989, M. forcipatum Ng, 1995 Ou and Yeo, 1995, M. pilosum Cai and Dai, 1999, M. amplimanus Dai, 1999, andM.…”
Section: Introductionmentioning
confidence: 71%
“…The diagnosis of nominal taxa has usually been based on a combination of quantitative and qualitative characters such as the proportion of rostrum, podomeres of second pereiopods and the presence and absence of pubescence on fingers, palm and merus of second pereiopods. Because of high morphological variation, the species diversity of M. pilimanus group has been debated (Cai et al 2004;Cai & Liang 1999;Hanamura et al 2011;Holthuis 1952;Johnson 1960;Li 2007;Wowor 2010;Wowor & Short 2007). Previously, the phylogenetic position refered by some M. pilimanus members also indicated the unclear relationship between congeneric species in genus Macrobrachium such as M. niphanae, M. yui and M. neglectum (Liu et al 2007;Wowor et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Where there was a mix of species, M. yui was identified based on the identification keys of Holthuis (1950), Liu et al (1990) and Hanamura et al (2011), and was separated from other shrimps caught in the Xuang River and Pho Stream. The sex of M. yui was determined by the size and the shape of the second cheliped (perepod 2) and the presence or absence of an appendix masculina on the endopod of the second pleopod.…”
Section: Sampling and Measuring Specimensmentioning
confidence: 99%
“…Therefore, it is difficult for us to determine clearly whether M. yui belongs to species with abbreviated larval development or those with extended larval development. However, M. yui has diverged from fluvial species according to the molecular phylogenetic tree of Wowor et al (2009) and the distribution area is scattered only in mountainous area of Indochina (Liu et al, 1990;Cai & Dai, 1999;Cai et al, 2004;Liu et al, 2007;Hanamura et al, 2011). This suggests that M. yui could be derived from fluvial species rather than amphidromous species, although this shrimp showed a few characteristics similar to amphidromous species.…”
Section: Biological Characteristics Of the Larvae And Evolution Of LImentioning
confidence: 99%
See 1 more Smart Citation